Student Motivation in First Aid Education for Burn - Rida Darotin; Eky Madyaning Nastiti; Feri Ekaprasetia; Yunita Wahyu Wulansari; Guruh Wirasakti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2026)
Background : Currently, there are wrong actions for provide in first aid for burns. However, burns can become a medical emergency if not treated properly. Infection, tissue damage is one of the sequelae that often appears. Motivation has considered as factors that can influence a person to provide first aid if there is a case of burns. Objective: The Object of this research is to determine differences motivation in first aid education for burn in SMPN 1 Kalisat. Methods : The method of this research used quasy-experiment with one group pretest-posttest design. The are 384 student for this population and the sample taken is 96 respondents using probability sampling techniques. The research instruments used documentary films and motivation questionnaires. This research test used the Wilcoxon tests. Results: Before screening the documentary film, motivation was in the strong category. After the screening of the documentary film, the students' motivation was in the strong category. Statistical test used Wilcoxon test with P Value < 0,05 that means there were differences in students' motivation before and after the screening of the documentary film on first aid for burns at SMPN 1 Kalisat. Conclusions: Student motivation can be increased with health education interventions in providing first aid for burns. This increased motivation is due to increasing the confidence and knowledge of students who receive health education in the form of documentary film.